An Evaluation of Longitudinal Measures of Anticholinergic Exposure for Application in Retrospective Administrative Data Analyses - Lozano-Ortega, Greta (Adv Ther, 2019)
INTRODUCTION: As continuous exposure to anticholinergics has been associated with adverse outcomes, accurately measuring exposure is important. However, no gold standard measure is available, and the performance of existing measures has not been compared. Our objective was to compare the properties of the Cumulative Anticholinergic Burden (CAB) measure against two existing measures of anticholinergic exposure and to assess their compatibility for use in observational studies based on claims data. METHODS: The average daily dose, cumulative dose and CAB measures were evaluated on: the applicability for use with anticholinergic burden scales, the ability to consider duration and/or accumulation of exposure, and consideration of anticholinergic dose, potency, and residual effect. To calculate each measure empirically, Truven MarketScan claims data from 2012 to 2015 were analyzed. Cumulative anticholinergic exposure over 1-year post-enrollment was calculated for each measure using Anticholinergic Cognitive Burden scale scores. Median [interquartile range (IQR)] and ranges of measure scores, and Spearman’s correlation coefficients between measures, were estimated. Due to the differing methods of calculation, the absolute values of each score cannot be compared. RESULTS: The properties of the different measures varied, with only the CAB considering both dose and theoretical potency. The cohort included 99,742 individuals (mean age = 73.1 years; 54.9% female). Among individuals prescribed anticholinergics (n = 55,969), 1-year median (IQR) scores based on average daily dose, cumulative dose and CAB measures were 0.9 (0.3–1.5), 16.9 (7.3–33.9) and 203 (68–500), respectively. Measures were highly inter-correlated (r(2) = 0.74-0.83). CONCLUSIONS: Considering both potency and dose, the CAB may prove a more comprehensive measure of anticholinergic burden; however, additional research is necessary to demonstrate whether it has any association with relevant health-related outcomes. FUNDING: Astellas Pharma Global Development, Inc. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12325-019-01035-z) contains supplementary material, which is available to authorized users.